Study Abroad: My Experience as an Exchange Student in China - Veal, Jenny (Journal of International Students, 2013)
Studying abroad is an opportunity to grow and test one’s limits. In the interest of encouraging other students to pursue international education I would like to share my experiences and the general bits of wisdom I gained along the way. I was inspired by and chose to study abroad due to my interest in foreign languages. In my life I have always had an unwavering dream. My dream was about equality, diversity and understanding. I grew up in a small town where everyone knew each other and everybody held some kind of prejudice. While people judged others I tended to wonder about cultural differences with intrigue. This led to my interest in foreign languages and culture. I always knew that I wanted to travel and study in Asia. I believe that in order for our society to work efficiently we must understand each other and embrace our differences.